Cyclooxygenase-1 haplotype C50T/A-842G does not affect platelet response to aspirin - Pettinella, Caterina; Romano, Mario; Stuppia, Liborio; Santilli, Francesca; Liani, Rossella; Davì, Giovanni (Thrombosis and Haemostasis, 2009)
COX-1 polymorphism C50T, in complete linkage disequilibrium with the other polymorphism A-842G, has been depicted as a determinant of pharmacological response to aspirin treatment. Whether these polymorphisms exert an effect on response to aspirin both in vitro and ex vivo is still controversial. We geno-typed a population of 148 healthy individuals for the C50T/A-842G haplotype. Thirty of them underwent low-dose aspirin (100 mg daily) treatment for four weeks and were followed up for seven days after withdrawal. In this subgroup, we evaluated the thromboxane-dependence of biochemical and functional indexes used to monitor the antiplatelet effect of low-dose aspirin. Among the 148 subjects studied, 10 were heterozygous for the C50T/A-842G haplotype (6.7%) and only one was homozygous for the 50T/-842G haplotype (0.67%). In the group on low-dose aspirin, serum thromboxane (TX) B2 as well as urinary 11-dehydro-TXB2 and arachidonic acid (AA)-induced aggregation were similarly suppressed in carriers and non-carriers of the 50T/-842G haplotype, with an increase until basal levels of all the parameters within seven days after withdrawal. We found no relationship between the 50T/-842G haplotype and the so-called phenomenon of aspirin resistance. Platelet cyclooxygenase activity, as reflected by serum TXB2, was uniformly and persistently suppressed by low-dose aspirin in both carriers and non carriers of these polymorphisms.
Keywords: Aspirin resistance; polymorphisms; pharmacogenetics